A simple theism for a mixed world: response to Bradley - Swinburne, R (Cambridge University Press, 2007)
In response to Michael Bradley, I summarize my account of the criteria by which the various data of natural theology increase the probability of theism and together make it probable. I explain the sense in which a simpler theory leaves less to be explained, justify my claim that God's perfect goodness is entailed by his other divine properties, and show that not merely is theism simpler than Bradley's 'Epicurean hypothesis', but that the 'mixed' data of natural theology are more to be expected given theism than given the 'Epicurean hypothesis'.